Peran Memori dalam Pemrosesan Bahasa : Tinjauan Psikolinguistik - Dwi Praptiwi; Dian Nurul Fitra (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Memory plays a vital role in language processing, impacting comprehension, production, and communication effectiveness. This essay examines the theoretical and practical aspects of the function of memory in psycholinguistics. This study, through qualitative analysis, identifies how memory systems interact with language processes. It also offers suggestions for future research. The results show that language processing efficiency is significantly influenced by the relationships between working memory, long-term memory, and short-term memory. Psycholinguistic theory and its applications in language education and therapy are strengthened by the findings of this study.